Online automatic identification of modal parameters of a bridge using p-LSCF Method - Filipe Magalhães (2009)
A concrete arch bridge over the Douro River, at the City of Porto in Portugal, is being monitored by twelve accelerometers since September 2007. The present paper describes in detail the methodology used to perform the on-line automatic identification of the modal parameters using the poly-Least Squares Complex Frequency Domain method (p-LSCF). The results obtained with this algorithm are compared with the ones obtained with the previously implemented Covariance driven Stochastic Subspace Identification method using one-year database.